UPAYA HUKUM DALAM PENYELESAIAN SENGKETA HAK KEKAYAAN INTELEKTUAL (Studi Kasus Putusan Nomor 41 PK/Pdt.Sus-HKI/2021) - Saraswati, Mardiana; Fuad, Fokky; Machmud, Aris (Lex Jurnalica, 2024)
AbstractThe law protects individuals and legal entities in certain cases to challenge a judge's decision as a forum for parties who are dissatisfied with a judge's decision that is deemed not to fulfill a sense of justice. In civil cases, legal remedies include ordinary legal remedies and extraordinary legal remedies. Extraordinary legal remedies are made for decisions that have permanent legal force (incracht van gewijsde), including a judicial review (request civil). This study aims to answer the formulation of the problem by analyzing the Copyright Law as a positive law in providing intellectual property protection for songwriters in Indonesia, and how other legal remedies can be made against decisions in the first instance court that have permanent legal force in copyright infringement cases. This study analyzes the copyright infringement of the song "Lagi Syantik" where the creator took legal remedies (litigation) at the Commercial Court, Cassation at the Supreme Court, and the final legal remedy of Resubmission at the Supreme Court. The method used is the normative legal research method and statute approach based on Law No. 28/2014 concerning Copyright, where moral rights and economic rights can be maintained as the creator's rights through legal remedies.Keywords: Legal Remedies, Copyright Infringement, Copyright of Song AbstrakUndang-undang melindungi seseorang maupun badan hukum dalam hal tertentu untuk melawan putusan hakim sebagai wadah bagi para pihak yang merasa tidak puas dengan putusan hakim yang dianggap tidak memenuhi rasa keadilan. Dalam perkara perdata, upaya hukum meliputi upaya hukum biasa, dan upaya hukum luar biasa. Upaya hukum luar biasa dilakukan atas putusan yang telah berkekuatan hukum tetap (incracht van gewijsde), termasuk Peninjauan Kembali (request civil). Penelitian ini bertujuan untuk menjawab rumusan masalah dengan menganalisis UUHC sebagai hukum positif dalam memberikan perlindungan kekayaan intelektual bagi Pencipta lagu di Indonesia, dan bagaimanakah upaya hukum lain dapat dilakukan terhadap putusan di pengadilan tingkat pertama yang telah inkracht dalam perkara pelanggaran Hak Cipta. Penelitian ini menganalisis pelanggaran Hak Cipta karya lagu “Lagi Syantik” dimana Pencipta menempuh upaya hukum (litigasi) di Pengadilan Niaga, Kasasi di Mahkamah Agung, dan upaya hukum terakhir Pengajuan Kembali di Mahkamah Agung. Metode yang digunakan adalah metode penelitian hukum normatif dan statute approach berdasarkan UU No 28/2014 tentang Hak Cipta, dimana hak moral dan hak ekonomi dapat dipertahankankan sebagai hak Pencipta melalui upaya hukum.Kata kunci: Upaya Hukum, Pelanggaran Hak Cipta, Hak Cipta Lagu